4x+9-49=0

Simple and best practice solution for 4x+9-49=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+9-49=0 equation:


Simplifying
4x + 9 + -49 = 0

Reorder the terms:
9 + -49 + 4x = 0

Combine like terms: 9 + -49 = -40
-40 + 4x = 0

Solving
-40 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '40' to each side of the equation.
-40 + 40 + 4x = 0 + 40

Combine like terms: -40 + 40 = 0
0 + 4x = 0 + 40
4x = 0 + 40

Combine like terms: 0 + 40 = 40
4x = 40

Divide each side by '4'.
x = 10

Simplifying
x = 10

See similar equations:

| -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 | | -2(2x+5)= | | 1x+2y+3z=18 | | (2x+13)=-81 | | 4(2x-6)= | | 17-13=2(x-6) | | 2u^2+2v^2+4=0 | | (2x-6)=28 | | 5(3c-1)-2=12c+2 | | -6x+12=2(3x-4) |

Equations solver categories